Durability study of electrospray deposited Pt film electrode for hydrogen production in PV assisted water electrolysis system - Chae, Sang-Youn; Yadav, Jyotiprakash B.; Kim, Kang-Jin; Joo, Oh-Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
We studied the durability of the previously reported low mass loaded, highly efficient electrospray deposited Pt film as a cathode and Ni mesh as anode electrode in PV assisted water electrolysis system for 1000 h. This assembly showed no detectable decline in performance for initial 200 h, but thereafter it started to decline with time and showed 18% decline after 1000 h. For conclusion, we analyzed the electrode surfaces by different analyzing techniques. Results showed that Pt film was detaching from the surface and there was a deposition of passive layer of Fe2O3 on edge side of cathode surface. The iron derivative might be come from the corrosion of the stainless steel connectors that we used in PV assisted water electrolysis system. The etching and oxidation of anode surface was also observed but it might not be responsible for deterioration of performance. Copyright (C) 2010, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GENERATION; ENERGY